2022
DOI: 10.1080/20008198.2022.2059999
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative trauma from multiple natural disasters increases mental health burden on residents of Fort McMurray

Abstract: Background Fort McMurray, a city in northern Alberta, Canada, has experienced multiple traumatic events in the last five years, including the 2016 wildfire, the 2020 floods, and the COVID-19 pandemic. Traumatic events often lead to increased mental health burdens in affected communities. Objective To assess if the number of traumatic events experienced by residents of Fort McMurray correlates with the prevalence and severity of mental health issues experienced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 69 publications
0
14
0
1
Order By: Relevance
“…A recent study in Fort McMurray reported that participants who experienced COVID-19, flooding, and wildfire traumas were four times more likely to have likely MDD, eleven times likely to have probable PTSD and eighteen times more likely to express GAD symptoms in comparison to the respondents who experienced COVID-19-only trauma [ 27 ]. Exposure to trauma increases the likelihood of PTSD, MDD and GAD, which invariably may increase the risk of suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Fort McMurray reported that participants who experienced COVID-19, flooding, and wildfire traumas were four times more likely to have likely MDD, eleven times likely to have probable PTSD and eighteen times more likely to express GAD symptoms in comparison to the respondents who experienced COVID-19-only trauma [ 27 ]. Exposure to trauma increases the likelihood of PTSD, MDD and GAD, which invariably may increase the risk of suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from the literature suggests the possibility that people with previous experience of serial traumatic events can build resilience as a result of post traumatic adaptation ( 59 ). While this phenomenon may potentially partly explain the lack of association found between trauma and self-reported cannabis abuse in Fort McMurray, our recent study suggests that Fort McMurray residents experienced a decline in resilience following these traumatic events ( 26 ). Conceivably, such induced low resilience may result in learned helplessness where residents coping mechanisms are diminished ( 60 ), including the (ab)use of cannabis or utilization of therapeutic interventions.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have focused on the exposure to traumatic events and the usage of substances (e.g., cannabis) leading to substance abuse (23)(24)(25). Fort McMurray residents have been exposed to various traumatic events including wildfire, flooding and the recent global pandemic which may lead to cannabis usage (26)(27)(28)(29). A study by Agyapong et al reported that participants in a cross-sectional study were more likely to abuse substances after the wildfire in Fort McMurray (24).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, cumulative exposure to a natural disaster and the COVID-19 pandemic is likely to exacerbate vulnerability to mental health difficulties. A previous study has found that people who have experienced both the COVID-19 pandemic and either floods or wildfires are more likely to have anxiety, depression and PTSD than those who have experienced only the COVID-19 pandemic [ 18 ]. Given that the onset of flooding and the lockdown in Zhengzhou occurred with a mere interval of eleven days, individuals there may not have fully recovered from flood-related disruptions when faced with the pandemic.…”
Section: Introductionmentioning
confidence: 99%